Method for quantitative analysis of the marker substrate ABCB1-protein fexofenadine in Caco-2 cell lysate - M. A. Kopanitsa; Yu. S. Tranova; I. V. Chernykh; A. V. Shchulkin; P. Yu. Mylnikov; O. V. Kalinkina; E. N. Yakusheva (LLC "Publisher OKI", 2023)
One way to analyze the activity of the ABCB1 protein is to assess the accumulation of its substrate fexofenadine (F.) inside the test cells. The goal is to develop and validate a method for the quantitative analysis of F. in Caco-2 cell lysate using HPLC-MS/MS. Materials and methods. Caco-2 cell lysate was used as a matrix. The analysis was performed on an "Ultimate 3000" chromatograph with a TSQ Fortis triple quadrupole mass detector, a UCT Selectra C18 4.6 mm*100 mm 5 µm column in a gradient elution mode. The mobile phase rate was 0.3 ml/min, the sample volume was 20 µl, the ionization mode was positive, and the internal standard was amantadine (ng/ml). Sample preparation - precipitation of cell lysate protein with acetonitrile. The method was validated for the following parameters: selectivity, linearity, lower limit of quantitation (LLOQ), correctness, precision, sample transfer and sample stability. Results. Chromatograms of the blank lysate of Caco-2 cells showed no peaks with retention times characteristic of F. (5.70 min) and amantadine (3.58 min). NPKO F. was 0.5 ng/ml. F.'s transfer did not exceed 20% of NPKO, and amantadine - 5%. Based on the results of the analysis of three series of calibration standards (0.5; 1; 1.5; 5; 10; 25; 40; 50 ng/ml), linear regression equations were obtained, the correlation coefficients exceeded 0.99. Accuracy and precision were assessed within and between cycles by analyzing F. solutions in the matrix (0.5; 1.5; 25 and 40 ng/ml) within three cycles. The parameters did not exceed 20% for LLPO and 15% for other points. The stability of F. solutions (1.5 and 40 ng/ml) in the lysate was analyzed during storage at room temperature, after 3-fold freezing-thawing, storage at -80 °C for 60 days, after sample preparation and being in the autosampler for 24 hours. The accuracy was within 15% of the nominal values. Conclusions. A method for the quantitative determination of F. in Caco-2 cell lysate using HPLC-MS/MS has been developed and validated.